Effectiveness of the prevention programme on posture and the incidence of back pain in primary school children: a pilot study - Marta Hojker; Jahnavi Vaishnav; Saša Staparski Dobravec (Zdravniški Vestnik, 2023)
Background: The incidence of back pain in childhood is rising and significantly impacts its incidence in adulthood. Important risk factors include poor posture, which is common due to a largely sedentary lifestyle. Our study aimed to determine the effect of a primary prevention programme on posture and pain incidence in primary school children.